Short Antimicrobial Peptide Derived from the Venom Gland Transcriptome of Pamphobeteus verdolaga Increases Gentamicin Susceptibility of Multidrug-Resistant Klebsiella pneumoniae - Cristian Salinas-Restrepo; Ana María Naranjo-Duran; Juan Quintana; Julio Bueno; Fanny Guzman; Lina M. Hoyos Palacio; Cesar Segura (MDPI AG, 2023)
Infectious diseases account for nine percent of annual human deaths, and the widespread emergence of antimicrobial resistances threatens to significantly increase this number in the coming decades. The prospect of antimicrobial peptides (AMPs) derived from venomous animals presents an interesting alternative for developing novel active pharmaceutical ingredients (APIs). Small, cationic and amphiphilic peptides were predicted from the venom gland transcriptome of Pamphobeteus verdolaga using a custom database of the arthropod's AMPs. Ninety-four candidates were chemically synthesized and screened against ATCC® strains of Escherichia coli and Staphylococcus aureus. Among them, one AMP, named PvAMP66, showed broad-spectrum antimicrobial properties with selectivity towards Gram-negative bacteria. It also exhibited activity against Pseudomonas aeruginosa, as well as both an ATCC® and a clinically isolated multidrug-resistant (MDR) strain of K. pneumoniae. The scanning electron microscopy analysis revealed that PvAMP66 induced morphological changes of the MDR K. pneumoniae strain suggesting a potential "carpet model" mechanism of action. The isobologram analysis showed an additive interaction between PvAMP66 and gentamicin in inhibiting the growth of MDR K. pneumoniae, leading to a ten-fold reduction in gentamicin's effective concentration. A cytotoxicity against erythrocytes or peripheral blood mononuclear cells was observed at concentrations three to thirteen-fold higher than those exhibited against the evaluated bacterial strains. This evidence suggests that PvAMP66 can serve as a template for the development of AMPs with enhanced activity and deserves further pre-clinical studies as an API in combination therapy.